Assessment of the Adequacy of Thyroid Hormone Replacement Therapy in Hypothyroidism - Brokhin, Matvey; Danzi, Sara; Klein, Irwin (Frontiers in Endocrinology, 2019)
Abstract Background: Recent studies identify a significant number of treated hypothyroid patients who express dissatisfaction with their therapy. At present there are sufficient measures of thyroid function to enable the clinician to establish a diagnosis of thyroid disease with a high degree of sensitivity and specificity. The purpose of this study was to quantitate the use of a new and novel assessment of clinically relevant hypothyroid symptoms in the management of patients with thyroid disease and to identify a tool that could help clinicians to assess adequacy of LT4 treatment. Methodology: Unselected outpatients of the Thyroid Clinic of the North Shore University Hospital at Manhasset completed a questionnaire asking them to rate their physical symptoms related to thyroid disease as part of their standard care. This questionnaire consisted of ten signs and symptoms. The questionnaire was collected from 198 control subjects, 241 subjects with primary hypothyroidism (under treatment), 113 euthyroid subjects (benign nodular thyroid disease), 73 previously hyperthyroid subjects (previously treated) and 27 subjects with thyroid cancer. A repeat questionnaire was obtained from 48 subjects with primary hypothyroidism (20%), 19 euthyroid subjects (17%) and 17 subjects previously hyperthyroid (23%) Data Analysis: The mean score for the sum of the signs and symptoms in the primary hypothyroid group with no medication change was 9.62 ± 1.29for the initial questionnaire, and 10.04 ± 1.32 for the follow up questionnaire (not significant). For the primary hypothyroid patients requiring a medication change, at the time of the initial questionnaire the mean serum TSH was 12.86 ± 2.75 mcU/ml. Concurrently with the normalization of TSH, a statistically significant improvement in the sum of signs and symptoms mean score for this group was noted (16.32 ± 1.93 initial vs. 10.32 ± 1.46 after treatment to normalize TSH). Conclusion: The proposed newly devised hypothyroid scale correctly identified subjects with TSH elevation and clinical/subclinical hypothyroidism based on their clinical signs and symptoms. In this particular subset of patients, the hypothyroid symptom scale showed a statistically significant improvement in the sum of the signs and symptoms with the normalization of the subjects’ thyroid function.